2016
DOI: 10.1371/journal.pone.0158987
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of CD154 with the α5β1 Integrin Inhibits Fas-Induced T Cell Death

Abstract: CD154, a critical regulator of the immune response, is usually associated with chronic inflammatory, autoimmune diseases as well as malignant disorders. In addition to its classical receptor CD40, CD154 is capable of binding other receptors, members of the integrin family, the αIIbβ3, αMβ2 and α5β1. Given the role attributed to integrins and particularly the β1 integrins in inhibiting apoptotic events in normal as well as malignant T cells, we were highly interested in investigating the role of the CD154/α5β1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 53 publications
4
16
0
Order By: Relevance
“…Cells were pre-incubated with different concentrations of sCD154 and then treated with the sub-optimum apoptosis-inducing concentration of TRAIL (50 ng/ml) or TNF-α (25 ng/ml) outlined above. Our data show that CD154 was capable of inhibiting TRAIL-and TNF-induced cell death in a dose-dependent manner (Fig 1D), as it did with Fas-induced response previously described [29]. It is important to mention here that we have shown before the capacity of agonistic anti-α5β1Abs to inhibit Fas-induced cell death in Jurkat E6.1cells as does CD154 [29], highly supporting the role of α5β1 integrin in the apoptosis-inhibiting effect of CD154 in Jurkat E6.1 cells.…”
Section: Plos Onesupporting
confidence: 86%
See 3 more Smart Citations
“…Cells were pre-incubated with different concentrations of sCD154 and then treated with the sub-optimum apoptosis-inducing concentration of TRAIL (50 ng/ml) or TNF-α (25 ng/ml) outlined above. Our data show that CD154 was capable of inhibiting TRAIL-and TNF-induced cell death in a dose-dependent manner (Fig 1D), as it did with Fas-induced response previously described [29]. It is important to mention here that we have shown before the capacity of agonistic anti-α5β1Abs to inhibit Fas-induced cell death in Jurkat E6.1cells as does CD154 [29], highly supporting the role of α5β1 integrin in the apoptosis-inhibiting effect of CD154 in Jurkat E6.1 cells.…”
Section: Plos Onesupporting
confidence: 86%
“…inactive form of α5β1, capable of binding CD154 [23], and that binding of sCD154 to these cells was completely abolished by soluble α5β1 confirming the specificity of sCD154 to α5β1 integrin [29].…”
Section: Plos Onementioning
confidence: 56%
See 2 more Smart Citations
“…This CD40‐VLA5 activated complex induces downstream signaling events, such as MAPK, p38, and ERK1/2, and has also been shown to syner‐gize in the release of inflammatory mediators, such as matrix metalloproteinase‐2 and ‐9, which suggests a crosstalk between these CD40L and VLA5 receptors (35). More recently, it has also been shown that the CD40L–VLA5 interaction promotes the survival of malignant T cells—as demonstrated by the activation of key survival signaling pathways, such as MAPKs (p38 and ERK1 /2) and PI3K—and resistance to Fasmediated apoptosis, an important hallmark of T‐cell malignancies (36).…”
Section: Discussionmentioning
confidence: 99%